SLR on Institutional Barriers and Resilience in Community-Based Tourism Governance - Pangesti Putri, Bintari; Raka Siwi Putri Utomo, Sherly; Chendraningrum, Dinarsiah (Integrasi Sains Media, 2026)
Despite the proliferation of Community-Based Tourism (CBT) as a sustainable development tool, its long-term viability remains precarious due to structural fragility and external disruptions. This Systematic Literature Review (SLR) investigates the institutional arrangements underpinning CBT resilience in Southeast Asia, addressing the gap between normative participation and actual sustainability. Guided by PRISMA 2020 protocols, the study synthesizes 34 high-impact, Scopus-indexed articles (2020–2025) through a rigorous three-stage coding process: open, axial, and selective. The findings demonstrate that CBT sustainability is not an inherent byproduct of community participation but an emergent institutional process. We propose a novel conceptual advancement: the CBT Institutional Resilience Framework, integrating three interdependent pillars: collaborative governance, social entrepreneurship, and institutional harmonization. This framework shifts the theoretical focus from utilitarian participation toward